Missouri ELL policies and mainstream teachers' preparedness perceptions: a three-article dissertation - Kearbey, John (My University, 2025)
This dissertation examined mainstream teachers' perceptions of preparedness to teach English Language Learners (ELLs) in Missouri's public schools through a three-article format, consisting of a systematic literature review, policy analysis, and quantitative evaluation. Grounded in Vygotsky’s Sociocultural Theory, Krashen’s Input Hypothesis, and Siemens’ Connectivism, the study addressed gaps between policy mandates and classroom realities amid increasing linguistic diversity. The first article reviewed 14 studies from 2003–2024, and revealed persistent under-preparation among mainstream teachers, influenced by inadequate pre-service training, variable professional development (PD), teacher beliefs, and institutional support. The second article traced Missouri's ELL policies from the Bilingual Education Act (1968) to the Every Student Succeeds Act (2015), and highlighted advancements like the ELL endorsement (5 CSR 20-400.570) and noted implementation inconsistencies, funding disparities, and rural-urban divides. The third article analyzed Missouri's First-Year Educator Survey data (2016–2024) using multiple linear regression and found that teachers rated their ELL preparedness lower than for other areas (R² = .1599 for teacher predictors), with principal evaluations showing limited alignment (R² = .0054). Findings underscored systemic gaps: teachers lacked SLA training, policies failed to ensure equitable resources, and rural districts struggled more than other districts. Implications included embedding ELL pedagogy in teacher preparation, mandating sustained PD, and reforming policies for better accountability. This work ultimately calls for equity-focused reforms to enhance ELL outcomes and sought to inform broader educational practice.
Keywords: Mainstream teacher preparedness; Professional development; Rural education; English Language Learners; English as a Second Language; Equitable resources